(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
In the article, it is emphasized that in modern society the health and comprehensive physical development of the younger generation are of great importance, and the role of sport in this process is invaluable. Children’s sports, particularly sports such as table tennis, not only improve children’s physical health but also support their mental, psychological, and social development. These types of sports provide excellent developmental opportunities for children, as they not only enhance physical strength but also contribute to improving intellectual and emotional well-being. The article presents ideas, reflections, and proposals related to these aspects.